(untitled) (Global Journal of Human-Social Science, 2021)
In Africa especially in Nigeria the issue of cultural clash and the dilemma involved in the process is one of the predominant themes largely treated by renowned writers such as Chinua Achebe 1958 Cyprian Ekwensi 1963 Elechi Amadi 1966 Wole Soyinka 1975 and Labo Yari 1978 to mention a few Using postcolonial theory as a potent analytical tool attempt is made in this paper to critically examine Aliyu Kamal s latest novel Somewhere Somehow 2019 and portray how he employs it to interrogate the tragic social and psychological effect of modernization colonialism The story elaborately discusses the issue of skin bleaching a corollary of colonialism which has become very pervasive among the uneducated ladies with dark skin in northern Nigeria Habi and Jiniya the heroines who blindly believe that boys particularly in Kano where the novel is set pine after light-skinned girls even if they were to appear as witches engage in bleaching that ultimately makes their skins like wankan tarwada a Hausa terminology that suggests an undefined colour The paper also depicts how marital peace eludes the bleachers homes in addition to the tragedy that befalls on them all as a result of aping western culture Jiniya dies due to skin cancer leukaemia and Habi suffers double tragedy divorce and miscarriage